Cardiovascular disease patients have increased risk for comorbidity: A cross-sectional study in the Netherlands - Candan Kendir; Marjan van den Akker; Rein Vos; Job Metsemakers (2017)
Comorbidity is a cause of increased mortality, decreased quality of life and increased use of healthcare services. It is important particularly for physicians and other healthcare providers in primary care settings to evaluate these patients properly. Cardiovascular diseases (CVD) are the most common cause of death from non-communicable diseases worldwide and are characterized by a high level of comorbidities.To address the distribution of CVDs and comorbidities across sociodemographic groups and associations between CVDs and comorbidities.A cross-sectional study was conducted using data of 67 786 patients. Data were collected by the Registration Network Family Practices (RegistratieNet Huisartspraktijken, RNH). Comorbidities were analysed using chi-square and logistic regression analyses.At the time of study, 26.5% of the patients had at least one CVD and 10.5% of patients had two or more CVD diagnoses. The strongest association within cardiovascular diseases were between health failure and arrhythmias (OR: 9.20; 95%CI: 7.78-10.89). Coronary artery disease and hypertension had strong relationship with diabetes (OR: 2.22; 95%CI: 2.02-2.45, OR: 2.22; 95%CI: 2.02-2.45 respectively) and lipid metabolism disorders (OR: 2.04; 95%CI: 1.87-2.23, OR: 2.04; 95%CI: 1.87-2.23, respectively). The strongest associations for cerebrovascular diseases were with epilepsy (OR: 4.09; 95%CI: 3.29-5.10) and arrhythmias (OR: 2.23; 95%CI: 1.99-2.50).One out of every four patients suffered from at least one CVD. Having one CVD increased the risk of another, co-occurring CVD and a higher number of other chronic diseases.